1994
DOI: 10.1107/s010827019300842x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and absolute configuration of a quinic acid–copper(II) complex

Abstract: In the title compound, catena-poly [(aquachloro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 4 publications
6
12
0
Order By: Relevance
“…This scenario is well illustrated by the X-ray crystal structure of the polymeric complex formed between Cu(II) and qaH, in which the ligand is coordinated via the 2-hydroxy acid (O 1 ,O 7 ) and the trans-diol (O 4 ,O 5 ) region. 70 As predicted, the ring protons lie well above [H(5i)] and below [H(4i)] the ligand plane, which is similarly reflected in the dihedral H-C-O-Cu angles (Table S2). Recent studies of the EPR spectra of species formed between Cr(V) and cis-or trans-1,2-cyclohexanediol have shown that the proton lying in the ligand plane couples to a greater extent with the unpaired electron on the Cr(V) ion, compared to the proton lying perpendicular to the ligand plane.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This scenario is well illustrated by the X-ray crystal structure of the polymeric complex formed between Cu(II) and qaH, in which the ligand is coordinated via the 2-hydroxy acid (O 1 ,O 7 ) and the trans-diol (O 4 ,O 5 ) region. 70 As predicted, the ring protons lie well above [H(5i)] and below [H(4i)] the ligand plane, which is similarly reflected in the dihedral H-C-O-Cu angles (Table S2). Recent studies of the EPR spectra of species formed between Cr(V) and cis-or trans-1,2-cyclohexanediol have shown that the proton lying in the ligand plane couples to a greater extent with the unpaired electron on the Cr(V) ion, compared to the proton lying perpendicular to the ligand plane.…”
Section: Discussionsupporting
confidence: 65%
“…In the case of trans -diol binding, the ring-protons lie above and below the ligand plane, resulting in limited overlap. This scenario is well illustrated by the X-ray crystal structure of the polymeric complex formed between Cu(II) and qaH, in which the ligand is coordinated via the 2-hydroxy acid ( O 1 , O 7 ) and the trans -diol ( O 4 , O 5 ) region . As predicted, the ring protons lie well above [H(5i)] and below [H(4i)] the ligand plane, which is similarly reflected in the dihedral H−C−O−Cu angles (Table S2).…”
Section: Discussionsupporting
confidence: 64%
“…The axial Cu(1)--O(5)(water) bond length of 2.424 (4)A. is in good agreement with the usual Cu- Acta Crystallographica Section C ISSN 0108-2701 01996 axial-O(water) distances in five-coordinate copper complexes (Allen, Kennard & Taylor, 1983;Tahirov, Lu, Shu & Chung, 1994;Bkouche-Waksman, 1994). The coordination effect is seen in a shortening of the C(14)~ 0(3) bond distance [1.272(5)A] compared with the corresponding bond length [1.313(5)A] in methyl 9hydroxy-9-fluorenecarboxylate (Liu, Huang & Wang, 1988).…”
supporting
confidence: 73%
“…The M–O distances observed in those complexes are in agreement with those seen in 1 and range from 2.052(2) to 2.164(2) Å (Zn II ) and 2.021(3) to 2.072(3) Å (Ni II ), while a wider range due to Jahn–Teller distortions is observed in the copper analog [1.969(3)–2.341(3) Å]. Equally comparable are the M–O distances occurring in the congener quinate complexes [Zn(C 7 H 11 O 6 ) 2 ],22 [Cd(C 7 H 11 O 6 ) 2 ] · H 2 O, [Cu(C 7 H 10 O 6 )(H 2 O)] 2 (H 2 O) 2, 23 {[Cu(NO 3 )(C 7 H 11 O 6 )(H 2 O)] · 2H 2 O} n , {[CuCl(C 7 H 11 O 6 )(H 2 O)] · H 2 O} n ,24 [Pt(C 6 H 14 N 2 )(C 7 H 10 O 6 )],25 and the trinuclear (NH 4 ) 2 {[V(O) 2 ] 2 [V(O)](μ‐C 7 H 10 O 6 ) 2 } · H 2 O 26…”
Section: Resultsmentioning
confidence: 99%